IMPROVED KNOWLEDGE ABOUT THE RISK OF HIV/AIDS IN ADOLESCENTS - Dewanti, Nisa; Diana, Meli (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: HIV/AIDS is still a public health problem worldwide and there is an increase in the number of teenagers affected by HIV/AIDS in the world. Teenagers are vulnerable to contracting HIV/AIDS because adolescence is a period of puberty which makes teenagers motivated to explore sexual experiences without using protection. The aim of this community service is to increase teenagers' knowledge about the risk of HIV/AIDS. Methods: The method used in this activity were counseling and giving presentations in class using audiovisual media at one of the vocational schools in Sidoarjo. The population is all vocational school's students who were members of health extracurriculars. The sampling used is total sampling of 50 students. The knowledge questionnaire was used as an instrument and its validity has been tested. Data were analyzed using descriptive analysis and the wilcoxon signed rank test. Results: Based on the data analysis, it can be concluded that there was a significant increase in knowledge after being given counseling about the risk of HIV/AIDS in adolescents (p<0.01). Conclusion:  The counseling about the risk of HIV/AIDS in Adolescents that has been carried out, it can be concluded that there is a significant difference in the average knowledge score before and after being given health education about the risk of HIV/AIDS in Adolescents.